Benign Sinonasal Masses: A Clinicopathological and Radiological Profile (Kathmandu University Medical Journal, 2014)
Background Benign nasal and paranasal sinus masses are commonly encountered in clinical practice. Though benign, certain nasal polyps, fungal sinusitis, hemangiomas and fibro-osseous tumors can present with locally destructive features and deformities, mimicking malignancies at once. Objective This study was carried out to recognize the great variety of benign nasal lesions and their frequency in our region. Methods A retrospective chart analysis of cases presenting as mass in nose and paranasal sinus that underwent surgery over three years duration at our institute was done. A provisional diagnosis was made after clinical assessment and radiological investigations, but the final diagnosis was established after histopathological examination. Results A total 331 cases presented as masses in nose and paranasal sinus presented during the period. The clinicopathological examination aided by endoscopic and imaging studies revealed the non neoplastic benign masses in 293 and neoplastic masses in 38. Polyps were the commonest lesions constituting 70% cases followed by rhinosporidiosis in 10%. Fungal sinusitis, squamous papillomas, hemangiomas and inverted papillomas were found to be in order of 4.5%, 4%, 3.5% and 3% respectively. Rare cases like “rhino-oto-cereberal” form of mucormycosis, angiomyoma, and psammomatoid ossifying fibroma were also observed in the study. Conclusion Most of the nasal polyps/fungal sinusitis can be diagnosed clinically. However many a times Computer tomography (CT) scan and biopsy are necessary to differentiate them from each other and treatment plan. Certain benign tumors have high potential for malignant transformation while others can present with locally destructive features and deformities. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11015 Kathmandu University Medical Journal Vol.11(1) 2013: 4-8